Scaling Gender and Nutrition Sensitive technologies and innovations in West and Central Africa: Lessons learnt from the Market for Agricultural Innovation and Technology - Segnon, Alcade C.; Obossou, Esdras; Moustapha, Belmira Y.; Ganyo, Komla Kyky; Kpadonou, G. Esaïe; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Scaling up Gender and Nutrition Sensitive (GNS) Climate-Smart Agriculture (CSA) technologies and Climate Information Services (CIS) is essential to reducing gender inequalities and empowering women in agriculture and food systems in West Africa. AICCRA collaborated with its regional partner, CORAF to promote tested and sound GNS Technologies during the 2023 Market for Agricultural Innovation and Technology (MITA). Thirteen (13) potential gender- and nutrition-sensitive CSA and CIS innovations available for scaling up were presented by AICCRA country clusters in West Africa focusing on dry land cereals and livestock in Senegal, rice-based systems in Mali and roots and tubers in Ghana. The event has resulted in an increased awareness of gender- and nutrition-sensitive CSA technologies and CIS, as well as their ability to strengthen agricultural sustainability and women's empowerment. The event has resulted in a significant number of country representatives committing to raise awareness and disseminate gender- and nutrition-sensitive CSA and CIS through various events such as seminars, workshops, conferences to different stakeholders including local farmers, processors, seed producers, communities, women's cooperative groups, projects, etc. Participants committed to mainstreaming gender and nutrition perspectives in research and development projects and ongoing interventions, as well as in the field when working with farmers.